2014
DOI: 10.1002/app.41359
|View full text |Cite
|
Sign up to set email alerts
|

Films made from poly(vinyl alcohol‐co‐ethylene) and soluble biopolymers isolated from municipal biowaste

Abstract: Blends were obtained from poly(vinyl alcohol-co-ethylene) and water-soluble biopolymers isolated from the alkaline hydrolysate of two materials sampled from an urban waste treatment plant: that is, an anaerobic fermentation digestate and a compost. The digestate biopolymers contained more lipophilic and aliphatic C and less acidic functional groups than the compost biopolymers. Evidence was obtained for a condensation reaction occurring between the biopolymers and the synthetic polymer. The thermal, rheologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
2

Year Published

2015
2015
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 29 publications
8
37
2
Order By: Relevance
“…Moreover, with extreme relevance for SBO-based products, farmers do not take transparency into account in their decisions. This result supports the efforts of other researches (e.g., Montoneri et al, 2011;Franzoso et al, 2015) aimed at finding out (marketable) SBOs from urban and agriculture wastes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, with extreme relevance for SBO-based products, farmers do not take transparency into account in their decisions. This result supports the efforts of other researches (e.g., Montoneri et al, 2011;Franzoso et al, 2015) aimed at finding out (marketable) SBOs from urban and agriculture wastes.…”
Section: Discussionsupporting
confidence: 88%
“…For instance, research carried out at the University of Torino over the last 7 years, has shown that urban and agriculture wastes are sources of soluble bio-based substances (SBOs). Plastic materials containing SBOs are particularly suitable for the manufacture of films for agricultural soil mulching (Montoneri et al, 2011;Franzoso et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas much research has been devoted to natural biopolymers from dedicated crop, little work has been carried out on biopolymers obtained from biowastes. Very recently, blends of soluble biopolymers (SBO) isolated from municipal biowastes and agriculture residues with poly vinyl alcohol‐ co ‐ethylene (EVOH) and poly ethylene‐ co ‐acrylic acid (PEAA) have been reported . The SBO were constituted by a pool of macromolecules with weight‐average molar masses (MWs) of 67 to 463 kDa, which contain aliphatic and aromatic C chains bonded to carboxylic, phenol, and amino groups.…”
Section: Introductionmentioning
confidence: 99%
“…For the EVOH–SBO blends prepared by solvent casting, a condensation reaction between the EVOH hydroxyl groups and the SBO PhOH functional groups was found to occur at 120°C. This led to the formation of a new material containing SBO covalently bonded to EVOH.…”
Section: Introductionmentioning
confidence: 99%
“…1.2); e.g. in the formulation of detergents-textile dyeing baths, emulsifiers [15], auxiliaries for soil/water remediation [16] and enhanced oil recovery [17], flocculants, dispersants and binding agents Solid residue recovered after 270 days aerobic biodegradation of plant residues UB CV T360 Solid residue recovered after 360 days aerobic biodegradation of plant residues for ceramics manufacture [11], nanostructured materials for chemical [18] and biochemical catalysis [19], plastic materials [20], soil fertilizers and plant biostimulants for agriculture [21,22] and animal feed supplements [23,24]. Such variety of applications is possible due to the fact that SBO is a mixture of molecules with molecular weights comprised in a wide range over 5 kD which contain a variety of functional groups (see virtual molecular fragments in Fig.…”
Section: Isolation Of Soluble Bio-based Substances (Sbo) From Urban Wmentioning
confidence: 99%